HASIL BELAJAR FISIKA SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN PROBLEM POSING DI KELAS X4 MAN 1 PEKANBARU - M. Rahmad; Denok Norhamidah; Fakhruddin Z (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2009)
This study aims to describe the results of student learning through the application of cognitive learningmodels problem posing in learning basic physics to materials and Vector Magnitude. The subject of thisresearch is the students at class X4 MAN 1 Pekanbaru, amounting to 35 people. Data collection instrumentof this research is to study the cognitive test results. Research data collection at the end of the process oflearning by doing tests of cognitive learning outcomes. Data were analyzed using descriptive analysistechniques including absorption power, the effectiveness of learning, student learning capacity and thecompleteness of completeness objectives of learning in a vector of the amount of material. The results of dataanalysis shows that the average absorption power was 80.6% of students in good categories, and theeffectiveness of learning with the media effectively enough, the completeness of classical learning of studentsis 80% with this category is not complete and the completeness of classical learning goal with 78.6% Thiscategory is not complete. So, the problem of learning models posing for raw materials is a vector quantityapplied to X4 MAN I Pekanbaru students cash terms of cognitive learning outcomes.